Y-type of Stenting for Revision of a Transjugular Intrahepatic Portosystemic Shunt (TIPS): A Case Report - Barakat, Fuad; Rössle, Martin; Reimer, Peter (British Journal of Healthcare and Medical Research, 2025)
Purpose: To describe the technique of y-stenting in a patient receiving TIPS revision for thrombotic shunt occlusion. Methods: This report describes a patient receiving TIPS for refractory ascites. At primary implantation, the stent migrated slightly towards the inferior caval vein, a plausible explanation for thrombotic stent occlusion and partial thrombosis of the inferior caval vein. Refractory ascites recurred indicating TIPS revision which was performed after a 2-week anticoagulation treatment. At revision, catheterization of the stent failed and a parallel TIPS was discussed, but eventually disregarded because of a very narrow intrahepatic portal branch which was completely occupied by the former Viatorr stent. Result: A y-type of stenting was performed by lateral puncture of the Viatorr stent and implantation of an additional stent through the wall of the primary stent. The intervention was uncomplicated, reduced the portosystemic gradient effectively, and resulted in complete clinical response. Conclusions and clinical significance: This case demonstrates the feasibility of y-stenting. The technique may be superior to parallel stenting because it avoids the risk of parenchymal and portal vein injury.